2002
DOI: 10.4049/jimmunol.169.9.5236
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin-α-Deficient Mice Make Delayed, But Effective, T and B Cell Responses to Influenza

Abstract: Lymphotoxin-α−/− (LTα−/−) mice are thought to be unable to generate effective T and B cell responses. This is attributed to the lack of lymph nodes and the disrupted splenic architecture of these mice. However, despite these defects we found that LTα−/− mice could survive infection with a virulent influenza A virus. LTα−/− mice and normal wild-type mice infected with influenza A generated similar numbers of influenza-specific CD8 T cells that were able to produce IFN-γ and kill target cells presenting influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 45 publications
8
74
0
Order By: Relevance
“…We found high levels of ex vivo CTL activity in cells from the lung and spleen, but little or no activity in cells from the DLN and NDLN. CTL activity in cells from the influenza-infected lung has been reported previously [13,33]. This lack of CTL activity in DLN agrees with Johnson et al [45], but they also found low CTL activity in the spleen.…”
Section: Discussionsupporting
confidence: 80%
“…We found high levels of ex vivo CTL activity in cells from the lung and spleen, but little or no activity in cells from the DLN and NDLN. CTL activity in cells from the influenza-infected lung has been reported previously [13,33]. This lack of CTL activity in DLN agrees with Johnson et al [45], but they also found low CTL activity in the spleen.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, while this minute proliferation was observed, our data clearly demonstrated that the absolute number of these cells in distal LNs during Ag aerosolization was extremely small. A number of reports have proposed the lung itself to serve as a site of Ag presentation and primary T cell priming to live replicating Ags (influenza virus infection) through the induction of bronchus-associated lymphoid tissue (65,66). However, the nature of the Ag is likely to be important, as we have previously shown that in mice devoid of LNs and spleen, the lung is unable to evoke Ag-specific primary immune responses to the model Ag, OVA (67).…”
Section: Discussionmentioning
confidence: 89%
“…Similar results were reported in the case of influenza virus infection of LTa-deficient mice, which also lack LN. LTa-deficient mice exhibited delayed immune responses to influenza virus and only survived at low infection doses that allow time for acquired immune responses to develop [29]. Thus, by employing a low MTB dose, we could exploit LTbRxSp-deficient mice as a model lacking SLO despite the demonstrated critical role of lymphotoxin signaling in TB [16,17].…”
Section: Discussionmentioning
confidence: 99%